Rheumatoid Arthritis disease activity assessment in routine care: performance of the most widely used composite disease activity indices and patient-reported outcome measures: Comparison of disease activity indices in RA - Salaffi, Fausto; Di Carlo, Marco; Farah, Sonia; Marotto, Daniela; Atzeni, Fabiola; Sarzi-Puttini, Piercarlo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: To evaluate the convergent and discriminative validity of many continuous composite disease activity indices and patient-reported outcome measures (PROMs) in rheumatoid arthritis (RA). Methods: In consecutive RA patients in moderate or high disease activity, according to the Simplified Disease Activity Index (SDAI) definition, were computed four additional composite disease activity indices, the 28-joint Disease Activity Score – erythrocyte sedimentation rate (DAS28-ESR), the Clinical Disease Activity Index (CDAI), the Chronic Arthritis Systemic Index (CASI), and the Mean Overall Index for RA (MOI-RA), and five PROMs, the Patients’ Activity Scale (PAS), the Rheumatoid Arthritis Impact of Disease (RAID), the 5-item RA Disease Activity Index (RADAI-5), the Routine Assessment of Patient Index Data (RAPID3), and the Clinical Arthritis Activity (PRO-CLARA). Spearman’s rho correlation coefficients were determined to assess their convergent validity, and discriminative performance was calculated by the area under the receiver-operating curve (AUC-ROC). The patients’ opinion of their symptomatic status (PASS) was used as the external criterion. Results: 246 RA patients with moderate (29.3%) or high disease activity (70.7%) have been assessed. The indices all showed a significant correlation (p